THE EFFECT OF TRAINING AND HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE MEDIATED BY INTRINSIC MOTIVATION: EVIDENCE FROM KARIANGAU FERRY PORT BALIKPAPAN, INDONESIA - Heriyawan`,; Sukisno Selamet Riadi; Siti Maria (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study investigates the influence of training and human resource development (HRD) on employee performance, with intrinsic motivation acting as a mediating variable. The research focuses on Kariangau Ferry Port Balikpapan, a public sector organization that plays a strategic role in regional logistics and maritime connectivity in Indonesia. Utilizing a quantitative methodology, data were collected from 41 employees, encompassing both operational and administrative staff. The analytical method employed was Partial Least Squares – Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The findings indicate that both training and HRD significantly enhance employee performance. Intrinsic motivation partially mediates the relationship between training, HRD, and performance, highlighting its crucial role in strengthening employees' internal drive to perform effectively. These results align with Self-Determination Theory, which posits that intrinsic motivation-shaped by autonomy, competence, and relatedness-is vital in sustaining performance improvement. Theoretically, this study contributes to the expansion of HRD and motivation literature within the context of public sector organizations, particularly in developing economies. Practically, the results offer managerial insights for designing targeted training and continuous development programs that foster intrinsic motivation and enhance the sustainability of employee performance in public service institutions.